A chlorin e6 derivative‐mediated photodynamic therapy for patients with cervical and vaginal low‐grade squamous intraepithelial lesions: a retrospective analysis. Issue 1 (19th July 2022) - Yao, Hongxia; Yan, Jia; Zhou, Zhongxia; Shen, Shuzhan; Wu, Yun; Liu, Pei; Zhang, Haiyan; Wang, Xiuli
Abstract: Cervical and vaginal low‐grade squamous intraepithelial lesions (LSIL) are associated with persistent human papillomavirus infections, and require an efficacious non‐invasive treatment such as photodynamic therapy due to anatomical characteristics. In this study, we evaluated the clinical efficacy and safety of a chlorin e6 derivative named STBF‐mediated photodynamic therapy (STBF‐PDT) for patients with cervical and vaginal LSIL. A total of 18 patients received STBF‐PDT for 3 to 6 times and followed up for 6 to 12 months; among them, 6 had cervical and vaginal LSIL and 1 had vaginal stump LSIL after hysterectomy for cervical cancer. Results showed the complete remission (CR) rates were 72.22% (13/18), and the HPV remission rates and HPV clearance rates were 88.89% (16/18) and 83.33% (15/18), respectively at 1‐month follow‐up. The CR reached 88.89% and HPV remission rates got 94.44% at the 6‐month follow‐up. There were no recurrence cases so far, and no pain, heaving sensation, scar, deformity, and any other obvious adverse reactions occurred during treatment and follow‐up. In conclusion, STBF‐PDT is an effective, safe, and well‐tolerated method for the treatment of cervical and vaginal LSIL. It may have promising potential for applications in the future. Abstract : The columnar dispersion optical fiber was prepared for cervical and vaginal photodynamic therapy.